EVALUATION OF TOXICITY OF CROCUS SATIVUS (SAFFRON) DURING EMBRYOGENESIS IN WISTAR RATS - RAMESH EDAMULA; M.DEECARAMAN; M.VIJAYALAKSHMI; D.P.SANTHOSH KUMAR; H.KRISHNAPPA (International Journal of Pharma and Bio Sciences, 2015)
Crocus sativus (saffron) is widely used as a food additive and as active components in many traditional medicine and modern pharmacology. Saffron is generally considered as a safe food additive and medicinal agent. However many studies carried out using pregnant mice have shown that saffron causes intrauterine growth retardation and induces embryonic malformations. Hence the present study was aimed to evaluate if a similar effect is seen in pregnant albino rats. In our experiment no deleterious effects were noted in the pregnant dams or on the fetuses up to the level of 500 mg/kg body weight dose.